Revolutionising high-rise building construction: the role of robotics in South Africa's construction industry - Ntebo Ngcobo; Opeoluwa Akinradewo (Journal of Construction Project Management and Innovation)
With the increased demand for high-rise buildings in urban areas, the construction industry is experiencing more accidents caused by workers carrying out construction at heights. Robotic technology has been adopted in the manufacturing industry over the years, which has reduced factory accidents. Therefore, this study explores the impact of robotics in constructing high-rise buildings in South Africa, focusing on productivity, safety, efficiency, and project management. The research investigates how robotics can revolutionise the industry by employing a quantitative research methodology, which involves surveys from professionals in the construction sector. The findings reveal significant benefits of robotics in enhancing productivity, reducing accidents, and improving construction quality. The study also identifies challenges such as high costs and lack of skilled labour for robotics operations. The exploration extends to robotics' influence on project timelines, cost management, and environmental sustainability. The implications of these findings are significant for stakeholders in the construction industry, suggesting a need for investment in research and development, training, and policy formulation to support the adoption of robotics. This research contributes to understanding the potential of robotics in transforming high-rise construction, particularly in emerging economies.